The Historical Soundscape of Monophonic Hi-Fidelity - Dineen, Murray (Current Musicology, 2014)
An article in High Fidelity magazine, entitled “Listening is Believing?” and dated July/August 1953, sets forth the contemporary limits of sound reproduction in the inimitable style of advertisement copy: “Technical electronics can go only so far. Te rest of the job must be done by the imaginative mind of the listener. Tat’s not a platitude; it’s a technical specifcation” (Campbell 1953, 28).1 The connection drawn between imagination and sound reproduction, that the imagination can be an aspect of “technical electronics,” is meant to salve the “imaginative mind of the listener.” In doing so, however, it betrays an anxiety: the relationship has gotten out of balance, with human imagination falling short in the face of advances in “technical electronics.” Te author, John Campbell, puts a frm boundary around the latter: it “can go only so far” (Campbell 1953, 28). But in this arrangement, human imagination is a supplement, an accessory to technology, not vice versa.2 I am indebted to Eric Barry for this source. ↵ This accessory role is not addressed by James Lastra’s otherwise useful distinction between fidelity and intelligibility. Postulating from Lastra’s account, let us say technology and imagination would be equal participants in sound reproduction. See Lastra 2012. ↵